2023
DOI: 10.1002/srin.202300140
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Behavior of Iron Ore Pellets during Reduction in H2 and N2/H2 Atmospheres at Different Temperatures

Oleksandr Kovtun,
Mykyta Levchenko,
Erik Oldinski
et al.

Abstract: The need to develop green steelmaking techniques has led to the replacement of reducing agents such as CO with H2. H2 and N2/H2 mixtures can be used for the carbothermal reduction of iron ore. Herein, the reduction swelling index (RSI) of iron ore pellets in a forming gas (N2/H2) atmosphere at temperatures of 700–1000 °C is investigated and it is compared with that in pure H2. It is showed in the experimental results that the RSI increases with increasing temperature for both the H2 and N2/H2 atmospheres. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…The Reduction Swelling Index (RSI) quantifies the increase in pellet volume during reduction and is known to rise with increasing temperature [58,105,106]. Scharm et al found that the RSI is significantly higher in an H 2 atmosphere compared to a CO atmosphere, peaking during the first stage of reduction (Figure 13) [58].…”
Section: Results Of Research Studies Focused On the Reduction In Iron...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Reduction Swelling Index (RSI) quantifies the increase in pellet volume during reduction and is known to rise with increasing temperature [58,105,106]. Scharm et al found that the RSI is significantly higher in an H 2 atmosphere compared to a CO atmosphere, peaking during the first stage of reduction (Figure 13) [58].…”
Section: Results Of Research Studies Focused On the Reduction In Iron...mentioning
confidence: 99%
“…Zhao et al observed that the RSI of pellets decreases with increasing H 2 content; they also noted that temperature has a more significant impact on swelling than the composition of the reducing atmosphere [105]. Kovtun et al found that the chemical composition and porosity of pellets significantly affect the RSI; specifically, pellets with lower gangue (CaO and SiO 2 ) content exhibited higher RSI at the same temperature [106]. Conversely, Sharma et al reported that an increase in gangue content leads to a decrease in RSI [108].…”
Section: Results Of Research Studies Focused On the Reduction In Iron...mentioning
confidence: 99%